Northwest History. Alaska, Glaciers. United States. (1937)
Defies Glacier. Defies Glacier. FAIRBANKS, Alaska,,Feb. 16. (/P)—A courageous Alaska woman defied the "runaway" Black Rapids glacier today to -frighten her from her roadhouse home, which lay in the path of the thundering Housework went on as usual for Mrs. H. E. Revell in Black Rapids roadhouse, threatened with eventual destruction if the glacier, less than a mile away, continues its advance.